Effects of Multimedia Framed Messages on Human Papillomavirus Prevention Among Adolescents. (January 2019) - Tu, Yu-Ching; Lin, Yi-Jung; Fan, Lir-Wan; Tsai, Tung-I; Wang, Hsiu-Hung
The purposes of this study were to develop gain-framed (benefits of performing behaviors) and loss-framed (costs of not performing behaviors) messages and to identify the effects of these messages on human papillomavirus (HPV)–related cervical cancer awareness and vaccination intention. Self-administered questionnaires and effect-size measurements were used to evaluate the effects of the framed HPV vaccination messages delivered through multimedia. The results showed that gain-framed and loss-framed messages equally improved HPV knowledge ( d = 2.147-2.112) and attitude toward HPV vaccination ( d = 0.375-0.422). The intent to receive HPV vaccinations for cervical cancer prevention was higher in the two intervention groups ( d = 0.369-0.378) in which the participants were informed that public funding for the vaccination was available. Participants who received loss-framed HPV education messages paid statistically significantly more attention to health education and expressed more concern for sexual health than participants who received gain-framed HPV education messages.